Revisión sistemática sobre la victimización en Colombia del pueblo Emberá (2023)
This work is a systematic review of the academic literature on the Emberá people. From written documents where different topics related to the community are exposed with the review of degree thesis, magazine articles and books about the Emberá Indigenous community and the situations that have affected their survival in the ancestral territory and their dignified life in other contexts throughout the years. In such a way, a synthesis of the collection of writings is made to form the exposed document, it is conformed by four essential pillars A. Education, B. Culture, C. Armed conflict and D. Health, to answer our research problem.